Detection of intestinal parasites and balantidium coli in farmed pigs in Kelantan via microscopy and molecular techniques - Ling, Foong Tong (Universiti Sains Malaysia, 2014)
Pigs are found throughout the tropical and temperate regions of the world. These animals are hosts to numerous intestinal parasites, which include the zoonotic Balantidium coli. Intestinal parasites cause detrimental effect to the growth rate and health status of pigs, which ultimately decrease the income of pig farmers. In addition, zoonotic parasite such as B. coli harbors by pigs may infect farmers and people who stay near pig farms. Hence, this preliminary study aimed to identify intestinal helminths and/or protozoa in pigs reared in Kelantan. An in-house duplex polymerase chain reaction (PCR) assay was developed to detect B. coli in the stool specimens. A total of 33 pig faecal specimens were randomly collected from farmed pigs in Kelantan. Direct wet mount and formalin ether concentration methods were used to examine the stool specimens for presence of intestinal parasites. DNA detection of B. coli was performed using an in-house duplex PCR assay that amplified l 8S rRNA gene of B. coli. Plasmodium falciparum gene was incorporated as the internal control to rule out the presence of PCR inhibitors in false negative DNA specimens. Results showed that 78.8% of the pigs were positive with one or more parasites. By direct wet mount, Ascaris sp., Trichuris ova-like sp., Balantidium-like cyst and other unknown parasites were found in 13 (39.4%), 3 (9.1%), 3 (9.1%) and 14 (42.4%) specimens, respectively. Formalin ether concentration method showed that 15 (45.5%) specimens were positive for Ascaris sp., 12 (36.4%) for Trichuris ova-like sp., and 17 (51.5%) contained unknown parasites. Interestingly, all the 3 positive stool samples for Balantidium-like cysts were negative for B. coli when screened with the in-house duplex PCR assay. In conclusion, this study showed that many of the local Kelantan pigs were infected with ascariasis and trichuriasis but none were infected with the zoonotic B. coli.